2020
DOI: 10.1186/s13017-020-00328-x
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic injury prognosis is more closely related to vascular injury severity than anatomical fracture complexity: the WSES classification for pelvic trauma makes sense

Abstract: Background: The most common cause of death in cases of pelvic trauma is exsanguination caused by associated injuries, not the pelvic injury itself. For patients with relatively isolated pelvic trauma, the impact of vascular injury severity on outcome remains unclear. We hypothesized that the severity of the pelvic vascular injury plays a more decisive role in outcome than fracture pattern complexity. Methods: Medical records of patients with pelvic fracture at a single center between January 2016 and December … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…In addition to stopping concomitant external and internal hemorrhage, the difficulty of open pelvic fracture treatment includes the management of severe wound infection and further sepsis and multiple organ failure [ 11 , 24 ]. The WSES guidelines suggest that the management of pelvic trauma must consider physiological and mechanical derangement [ 17 , 19 ]. An international validation using the National Trauma Data Bank proved that the WSES guidelines were an accurate and reproducible classification system for pelvic injuries [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to stopping concomitant external and internal hemorrhage, the difficulty of open pelvic fracture treatment includes the management of severe wound infection and further sepsis and multiple organ failure [ 11 , 24 ]. The WSES guidelines suggest that the management of pelvic trauma must consider physiological and mechanical derangement [ 17 , 19 ]. An international validation using the National Trauma Data Bank proved that the WSES guidelines were an accurate and reproducible classification system for pelvic injuries [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, vascular injury was also found in 7–10% of stable pelvic fractures, which have often been considered minor injuries and are normally treated conservatively [ 14 , 15 ]. Some of these fractures even require angioembolization to achieve hemostasis [ 9 , 14 , 16 ]. Not only mechanical stability but also associated vascular injury should be evaluated in the management of pelvic fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Not only mechanical stability but also associated vascular injury should be evaluated in the management of pelvic fracture. Wu et al reported that vascular injury severity is more closely correlated with the outcome than the type of anatomical fracture of the pelvis [ 9 ]. Our previous study, which was based on a single institution experience, also showed that the role of pelvic stability is not significant when evaluating associated hemorrhage in the management of patients with pelvic fracture [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the anatomical description of the Young and Burgess classification does not aid in determining the prognosis of a pelvic fracture patient. To this extent the World Society of Emergency Surgery (WSES) classification has been proposed and validated (7). This classification stratifies patients according to vascular injury severity in combination with the mechanical instability of the pelvic ring.…”
Section: Introductionmentioning
confidence: 99%